Optimize the Preparation of Novel Pyrite Tailings Based Non-sintered Ceramsite by Plackett-Burman Design Combined With Response Surface Method for Phosphorus Removal - Chen, Ruihuan; Pan, Zhenlin; Chu, Shuyi; Xiao, Jibo; Weng, Rengui; Ouyang, Da; Yang, Yunlong; Wu, Xiangting; Huang, Zhida (Frontiers in Chemistry, 2022)
The large amount of untreated pyrite tailings has caused serious environmental problems, and the recycling of pyrite tailings is considered as an attractive strategy. Here, we reported a novel non-sintered ceramsite prepared with pyrite tailings (PTNC) as the main active raw material for phosphorus control, and the dosage effect of ingredients on total phosphorus (TP) removal ability was investigated. The results from Plackett-Burman Design (PBD) suggested the dosages of dehydrated sludge, sodium bicarbonate and cement were the factors which significantly affect the TP removal ability. The Box-Behnken Design (BBD) based response surface methodology was further employed, and which indicated the interactions between different factors, and the optimized recipe for PTNC was 84.5 g (pyrite tailings), 10 g (cement), 1 g (calcined lime), 1 g (anhydrous gypsum), 3 g (dehydrated sludge) and 0.5 g (sodium bicarbonate). The optimized PTNC was characterized and which presented much higher specific area (7.21 m2/g) than the standard limitation (0.5 m2/g), as well as a lower wear rate (2.08%) rather than 6%. Additionally, the leaching metal concentrations of PTNC were far more below the limitation of Chinese National Standard. The adsorption behavior of TP on PTNC was subsequently investigated with batch and dynamic experiments. It was found that the calculated max adsorption amount (qmax) was about 7 mg/g, and PTNC was able to offer a stable TP removal ability under different hydraulic retention time (HRT). The adsorption mechanism was discussed by model fitting analysis combined with XRD and SEM characterization, and cobalt phosphide sulfide was observed as the newly formed substance through the adsorption process, which suggested the existing of both physical and chemical adsorption effect. Our research not only offered a economic preparation method of ceramsite, but also broaden the recycling pathway of pyrite tailings.